Experimental study on durability properties of kenaf fibre-reinforced geopolymer concrete - Noor Abbas, Al-Ghazali; Abdul Aziz, Farah Nora Aznieta; Abdan, Khalina; Mohd Nasir, Noor Azline; Fahim Huseien, Ghasan (Elsevier, 2023)
The use of fibres in concrete has attracted the interest of many researchers to improve the tensile properties of geopolymer concrete. While adding natural fibres has gained popularity as an eco-friendly alternative to synthetic fibres. This combination of natural fibre-reinforced geopolymer concrete is an interesting composite that has not been reported by many, particularly when kenaf fibre is applied. Hence, this article aims to understand the performance of kenaf fibre-reinforced geopolymer concrete (KFRGC) in terms of water absorption, porosity, sorptivity, water penetration, and resistance against chloride ions penetration and chemical attacks. The results showed that the addition of KF increased the porosity of the geopolymer, thus increasing the water absorption-related properties. It’s observed that the porosity tends to increase with increasing length and volume content of fibres. Compared to control specimens, the highest increment (12.5%) in the porosity was recorded with specimens prepared with a 1.5% volume of fibre and a length of 40 mm. Likewise, the water permeability reading increased with increasing volume and fibre length in the geopolymer matrix. In specimens containing 1.5% fibre, increasing the length of fibre from 20 to 30 mm caused an increment in water permeability from 7.42 cm to 8.9 cm, respectively. However, the chloride, sulphate and acid resistance could be improved due to the ability of the fibres to bridge across the cracks. Furthermore, increasing the length of the fibre to 40 mm, reduced the acid resistance of the proposed concrete and increased the loss of strength to 16.3% and 19.2% at the age of 180 and 365 days, respectively. The outcomes of this research show that using kenaf fibres as a fibrous material in the production of environmentally friendly and durable concrete has a promising future.